2016
DOI: 10.1080/09168451.2015.1086261
|View full text |Cite
|
Sign up to set email alerts
|

Search for aflatoxin and trichothecene production inhibitors and analysis of their modes of action

Abstract: Mycotoxin contamination of crops is a serious problem throughout the world because of its impact on human and animal health as well as economy. Inhibitors of mycotoxin production are useful not only for developing effective methods to prevent mycotoxin contamination, but also for investigating the molecular mechanisms of secondary metabolite production by fungi. We have been searching for mycotoxin production inhibitors among natural products and investigating their modes of action. In this article, we review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…To reach such ambitious objectives, many preventive strategies have been developed to reduce AFB1 occurrence in food commodities. These strategies range from good agricultural practices to the use of biocontrol agents or natural compounds able to block toxin production [10]. Even if the exact mechanism of action has not yet been completely elucidated, a few studies already demonstrated that some of these natural products can inhibit AFB1 production by a transcriptional down-regulation of the genes involved in AFB1 synthesis [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…To reach such ambitious objectives, many preventive strategies have been developed to reduce AFB1 occurrence in food commodities. These strategies range from good agricultural practices to the use of biocontrol agents or natural compounds able to block toxin production [10]. Even if the exact mechanism of action has not yet been completely elucidated, a few studies already demonstrated that some of these natural products can inhibit AFB1 production by a transcriptional down-regulation of the genes involved in AFB1 synthesis [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Even if several approaches have been developed to limit AFB1's contamination (Wild et al 2015;Jalili, 2015), they remain insufficient to completely avoid mycotoxin contamination thus emphasizing the need to develop new strategies to guarantee food safety. The use of natural products such as spices, plant extracts or essential oils with anti-aflatoxinogenic properties represent a complementary or alternative strategy against mycotoxin contamination (Annis et al, 2000;El Khoury et al, 2017;Holmes et al, 2008;Sakuda et al, 2016). For instance, piperine, a major active component of black and long peppers (Piper nigrum L. and…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying specific inhibitors of aflatoxin production as possible candidates for drugs to prevent aflatoxin contamination of foods without incurring the rapid spread of resistant strains 4) . These inhibitors are also useful biological probes to clarify the regulatory mechanism for aflatoxin production in aflatoxigenic fungi.…”
Section: Introductionmentioning
confidence: 99%